Regionalism and Decentralization - Čiplić, Svetozar (Zbornik radova Pravnog fakulteta u Novom Sadu, 2016)
The paper analyses different models of decentralization that are proposed by the expert teams, certain political parties and government bodies. The essence of the analisis is to define the elements of a rationalized regionalization.